If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -50 = -150 Reorder the terms: -50 + 10y = -150 Solving -50 + 10y = -150 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + 10y = -150 + 50 Combine like terms: -50 + 50 = 0 0 + 10y = -150 + 50 10y = -150 + 50 Combine like terms: -150 + 50 = -100 10y = -100 Divide each side by '10'. y = -10 Simplifying y = -10
| x-3y=29 | | 50x^2=98 | | 5/9n-2=2/3n | | -14=-7x+2(6x-22) | | 2x=6.8 | | 7(6-3x)+2= | | 72=4.5n | | -4v-2v-16=38 | | lnx+ln(x+5)=ln(8x+10) | | -x-42=-3x+14 | | 5(-x+7)=20 | | 10-5(9n-9)=10-5 | | 6y-2=-3 | | 20y^2+9y-20=0 | | 04(1.5c+6)-2c=-9 | | x-20=60 | | 3x+6y+4z=2900 | | 7x-11=3x-3 | | 140=192-w | | -3x+6(2x+9)=9 | | 5x-34=17 | | x+10=400 | | 2x+3x+15=30 | | 3+2n= | | 125=-w+236 | | -2r+6(r-1)+3r-(4-r)=(r+5)-5 | | 4-7j=f-12 | | 1+1=8 | | -v+61=185 | | (7t-2)(-3t+1)=-3(1-3t) | | 22-6=4h | | 85+17x=-87+13x |